Governance and Development Outcomes in Asia - Kunal Sen (Asian Development Bank (ADB), 2014)
The relationship between governance and economic development is one of the most important areas of research in international development. Much of the previous literature has focused on whether better governance leads to higher levels of income. In this paper, we examine the relationship between governance and broader development outcomes, with a specific focus on developing Asia. In our empirical analysis, we use disaggregated measures of governance to capture different dimensions of governance, and to allow for the possibility that different dimensions of governance such as administrative capacity, legal infrastructure, and state accountability can affect development indicators differentially. We find a clear role for governance in affecting most development outcomes except levels of schooling. This is particularly evident for state administrative capacity and legal infrastructure, and less evident for state accountability. However, we find that the benign relationship between governance and development is weaker for Asian countries for several of the development indicators. We also find that the key mechanism by which governance affects development is by increasing the mobilization of domestic resources and by increasing the effectiveness with which these resources are spent on social sectors. Along with the fact that governance quality is lower in Asia than other regions of the world (except sub-Saharan Africa), this suggests that improvements in governance along with the strengthening of the mechanisms by which governance affects social development can deliver clear gains in development outcomes in developing Asia.
hdl:11540/4229
Keywords: I30; O11; O53; 330; governance; development outcomes; Asia